The bahá‟í faith and is contribution to interreligious dialogue - Pérez G., Jenny (Cuadernos Judaicos, 2017)
“The well-being of mankind, its peace and security, are unattainable unless and until its unity is firmly established”4 it is the fundamental principle that moves Bahá'ís around the world. Bahá'u'lláh, the Founder of the Bahá'í Faith, said that to achieve world‟s unity it is necessary for humanity to recognize that there is only one God, that is, that all religions come from the same divine source. Other important principles are equality between men and women, the elimination of all forms of prejudice, harmony between science and religion, the need for education for all and the elimination of the extremes of wealth and poverty.Interreligious dialogue creates an environment that allows exploring how religion can be a force of cohesion, of unity in society and as a system of knowledge, which along with science, promotes the development of civilizations. From this perspective, religion through the different stages that humanity has lived, whether in the times of Krishna, of Moses, of Jesus, of Buddha, of Muhammad or more recently of Bahá'u'lláh, has helped to refine the capacity to achieve spiritual well-being while achieving social progress.Thus, under the perspective of unity that the Bahá'í Faith urgesíthrough interreligious dialogue one can look at the other harboring the hope of seeing “the human race as one soul and one body, to humanity as one family, and to humanity as the fruits of one tree and the leaves of one branch."5 In this document, the concept of unity is analyzed as the basis for such dialogue and for the contribution of religion in society. In addition, three elements that bring the concept of unity to practice are briefly presented: equality between men and women, harmony between science and religion, and consultation. It concludes with a short description of a case in which interreligious dialogue is put into action to create a code of ethics, capable of enhancing a culture of peace and acceptance while promoting the common good in our society.